2009
DOI: 10.1111/j.1600-0404.1996.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epilepsy, seizures and epileptiform EEG discharges on cognitive function

Abstract: Several relationships have been obtained between cognitive impairment and epilepsy-related or treatment related factors. One of these factors is treatment-related: the central cognitive side effects of the antiepileptic drugs (AEDs). The second and third factors are disease-related factors , i.e., the effect of the seizures and underlying epileptiform discharges in the brain and the localization of the epilepto-genic focus in specific areas of the brain. Although most cog-nitive problems have a multifactorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…However, the extent of neuronal loss and the severity of cognitive deficits in this group were far less striking than those observed in the rats that had experienced motor SE. Thus, our findings add further weight to the evidence from former studies in animal models [9], [53] and humans [4], [6], [63] showing that behavioral deficits in TLE correlate with the extent of hippocampal damage.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the extent of neuronal loss and the severity of cognitive deficits in this group were far less striking than those observed in the rats that had experienced motor SE. Thus, our findings add further weight to the evidence from former studies in animal models [9], [53] and humans [4], [6], [63] showing that behavioral deficits in TLE correlate with the extent of hippocampal damage.…”
Section: Discussionsupporting
confidence: 84%
“…It has also been repeatedly reported that TLE patients with hippocampal sclerosis may show learning and memory deficits, increased anxiety, depression and mood disorders [4], [5], [6]. Thus, it seems reasonable to assume that these behavioral changes are secondary to the TLE-related hippocampal neurodegeneration.…”
Section: Introductionmentioning
confidence: 96%
“…The mechanisms underlying the improvement in cognitive function by LEV remain unknown. It is thought that it may act by controlling seizures and suppressing epileptiform discharges 12. The pharmacological properties of LEV may include neuroprotective effects against brain insults 13.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalography of CSWS typically consists of continuous spike-waves, generalized or focal, in slow-wave sleep. Some studies only detected generalized discharges [34]; Binnie et al [35] found both generalized and focal discharges, and Chez et al [29] described primarily focal epileptiform abnormalities. In our study, the discharges were focal in 76% of the patients, multifocal in 12%, and generalized in 12%.…”
Section: Discussionmentioning
confidence: 98%